Ethylene management during controlled atmosphere storage of 'Laetitia' plums Manejo do etileno durante o armazenamento de ameixas 'Laetitia' em atmosfera controlada - de Alves E.O.* (2009)
The objective of this research was to evaluate the effects of treatment with 1-methylcyclopropene (1-MCP) and different ethylene concentrations in the storage room on f 'Laetitia' plums quality stored under controlled atmosphere. The treatments evaluated were 1-MCP application (1.0μL L-1) and ethylene (C2H4) in the concentrations <0.04μL L-1, 1.0μL L-1, and 10μL L-1 inside the CA storage (1.0kPa of O2+3.0kPa of CO2/0.5oC±0.1oC and 95±2% RH) of. Respiratory rates were lower in fruits treated with 1-MCP and stored at 10μL L-1 of C2H4. Fruits treated with 1-MCP showed the lowest ethylene production rates. At removal from CA storage, fruits treated with 1-MCP and stored at C2H4 concentration <0.04μL L-1 showed higher flesh firmness and fruit compression resistance and lower flesh browning incidence. After shelf life, fruits treated with 1-MCP had the highest flesh firmness. Titratable acidity was higher in fruit treated with 1-MCP and left in CA storage with <0.04μL L-1 C2H4 concentration. 1-MCP and ethylene absorption delay ripening and reduce flesh browning incidence in 'Laetitia' plums. The effects of 1-MCP persist during shelf life. However, even with the use of these technologies, flesh browning occurrence does not allow fruit storage for 60 days under de CA storage condition used.